A UV / moisture dual-curing triple-proof adhesive and its preparation method and application
Through the coordinated combination of alkoxysilane-modified acrylate oligomers and phosphorus-containing acrylates, combined with ultraviolet light and moisture dual curing technology, the existing triple-proof adhesives are solved in the balance between flame retardant performance and adhesion. The problem is that high adhesion and high flame retardancy adhesives are achieved, suitable for the protection of printed circuit boards, and reduce the preparation cost.
Patent Information
- Application Number
- CN202411216876.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-02
AI Technical Summary
The existing ultraviolet cured triple-proof adhesives are difficult to balance the flame retardant performance and adhesion, and there is a lack of adhesives with high adhesion and high flame retardancy suitable for large-scale industrial production.
Through the synergistic combination of alkoxysilane-modified acrylate oligomers and phosphorus-containing acrylates, a composition with a synergistic flame retardant effect of silicon-phosphorus is formed. Combined with ultraviolet light and moisture dual curing technology, a combination of both the same A triple-resistant adhesive with high adhesion and high flame retardancy.
It realizes flame retardant grade and level 0 adhesion of UL94-V0, meets the requirements of spraying process, has good leveling, is suitable for the protection of printed circuit boards, and reduces the preparation cost and meets environmental protection requirements.
Smart Images

Figure SMS_8 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to an ultraviolet light / moisture dual-curing triple-proof adhesive and a preparation method and application thereof. Background Art
[0002] With the continuous development of aerospace, aviation, ships, carrier communications and electronic technology, the corresponding products or their components are usually required to be able to work in special environments of high temperature, high humidity, and high salt fog, and have high reliability. Due to working in a special corrosive environment, products and their components are prone to condensation, metal corrosion, mildew of non-metallic materials and other problems. Therefore, in order to improve the environmental adaptability of products and their components and ensure the long-term use of products in harsh environments, more and more manufacturers have begun to use three-proof adhesives to protect electronic devices. At the same time, for safety considerations, more and more manufacturers require three-proof adhesives for electrical device protection to have good flame retardant properties, and some manufacturers even require the flame retardant grade of three-proof adhesives to reach UL94-V0 grade.
[0003] Since the three-proof adhesive must meet the specific low viscosity spraying process requirements and the performance requirements of high adhesion to the printed circuit board (PCB), most of the UV-cured three-proof adhesives on the market generally do not have flame retardant properties. However, if the flame retardant properties of the three-proof adhesive need to be increased, the usual method is to add phosphorus-containing flame retardants. If a small amount of solid or liquid flame retardants are added, the flame retardant effect will not meet the requirements. At the same time, the addition of a large amount of solid phosphorus-containing flame retardants will also cause the viscosity of the three-proof adhesive to be too high, resulting in poor leveling and reduced adhesion. In addition, the addition of a large amount of liquid phosphorus-containing flame retardants will lead to reduced adhesion to the PCB. At the same time, since the liquid flame retardant itself does not participate in the cross-linking reaction, long-term use will cause the liquid flame retardant to migrate to the surface of the cured film, thereby reducing the flame retardant effect. At present, many scholars have also studied flame retardant three-proof adhesives. The published patent CN110885625A discloses a method for preparing a flame retardant UV-moisture dual-curing polyurethane acrylate three-proof paint. Although the three-proof paint prepared by this method has certain flame retardancy, the synthesis of the phosphoric acid ester polymer is complex and the cost is high, which is not conducive to large-scale industrial production. Based on this, it is necessary to develop a UV / moisture dual-curing three-proof adhesive with high adhesion and flame retardancy and suitable for large-scale industrial production based on the urgent needs of the current market. Summary of the invention
[0004] The purpose of the present invention is to provide a UV / moisture dual-curing three-proof adhesive to solve the defects of high adhesion and low flame retardant effect or low adhesion and high flame retardant effect of the UV-curing three-proof adhesive on the existing market.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned UV / moisture dual-curing triple-proof adhesive.
[0006] Another object of the present invention is to provide an application of the above-mentioned UV / moisture dual-curing triple-proof adhesive.
[0007] To this end, the technical solution of the present invention is as follows:
[0008] A UV / moisture dual-curing conformal adhesive comprises, by weight, 20 to 35 parts of alkoxysilane-modified acrylate oligomer, 20 to 50 parts of phosphorus-containing acrylate, 30 to 70 parts of acrylic reactive diluent and 2 to 10 parts of photoinitiator; wherein:
[0009] The alkoxysilane-modified acrylate oligomer is an oligomer with a viscosity of 5000mPa·s to 10000mPa·s obtained by copolymerizing monomer I, monomer II and monomer III, wherein monomer I is ethylene glycol diglycidyl ether and / or polyethylene glycol diglycidyl ether, monomer II is acrylic acid or methacrylic acid, and monomer III is an alkyl orthosilicate; the phosphorus-containing acrylate is at least one of diethyl methyl phosphate acrylate, diethyl ethyl phosphate acrylate and diethyl methyl phosphate methacrylate; and the weight ratio of the alkoxysilane-modified acrylate oligomer to the phosphorus-containing acrylate is (0.8 to 1.25):1.
[0010] Among them, the chemical structure formula of the alkoxysilane-modified acrylate oligomer is:
[0011] ,
[0012] In the formula, R1 each independently represents a C1-C3 alkyl group, R2 each independently represents H or a methyl group, and n is an integer ranging from 1 to 10; preferably an integer ranging from 1 to 5.
[0013] The chemical structural formula of ethylene glycol diglycidyl ether and / or polyethylene glycol diglycidyl ether is:
[0014] ,
[0015] In the formula, n is an integer in the range of 1 to 10, preferably 1 to 5.
[0016] Preferably, the preparation method of the alkoxysilane-modified acrylate oligomer is:
[0017] S1. Add monomer I into a three-necked flask, introduce nitrogen after evacuating, gradually heat to 100°C~130°C under stirring, and slowly add monomer II and inhibitor during the heating process; react the reaction mixture at 70°C~90°C for 10h~12h to prepare prepolymer A;
[0018] S2. The prepolymer A, alkyl orthosilicate and catalyst are heated to 80° C. in a vacuum environment with nitrogen gas introduced, and stirred for reaction for 5 h to 6 h to prepare an alkoxysilane-modified acrylate oligomer that is dual-cured by UV light and moisture.
[0019] Preferably, in step S1, the molar ratio of monomer I to monomer II is 1:(2-3).
[0020] Preferably, in step S1, the inhibitor is p-hydroxyanisole, p-benzoquinone, hydroquinone or naphthoquinone; and the amount of the inhibitor added is 0.001 of the molar amount of monomer I.
[0021] Preferably, in step S2, the alkyl orthosilicate is methyl orthosilicate, ethyl orthosilicate or propyl orthosilicate; and the molar ratio of prepolymer A to the alkyl orthosilicate is 1:(1-1.3).
[0022] Preferably, in step S2, the catalyst is dibutyltin dilaurate; and the amount of the catalyst added is 0.3wt.% to 0.4wt.% of the weight of the prepolymer A.
[0023] Preferably, the acrylic reactive diluent is at least one of tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, isobornyl acrylate, isobornyl methacrylate, and propylene glycol monomethyl ether diacrylate.
[0024] Preferably, the photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenylpropanone (referred to as photoinitiator 1173), 1-hydroxy-cyclohexyl-phenyl ketone (referred to as photoinitiator 184), and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (referred to as photoinitiator TPO).
[0025] In the UV and moisture dual-curing triple-proof adhesive of the present invention, a composition with synergistic effect is obtained by modifying the traditional component acrylate with alkoxysilane and then compounding the modified alkoxysilane-modified acrylate oligomer with phosphorus-containing acrylate.
[0026] Specifically, in the synergistic composition, in the alkoxysilane-modified acrylate oligomer, the alkoxysilane-modified part provides a moisture-curing group, which can form a molecular bridge with the PCB substrate during the curing process to increase the adhesion to the substrate; at the same time, it has been verified through experiments that the silicon element introduced in the alkoxysilane-modified acrylate oligomer in the adhesive can also combine with the phosphorus element with flame retardant effect introduced by the phosphorus-containing acrylate to form a silicon-phosphorus synergistic flame retardant effect, and obtain substantially the same flame retardant effect while reducing the addition ratio of phosphorus-containing acrylate in the traditional three-proof adhesive component, or obtain significantly better flame retardant effect while adding the same ratio of phosphorus-containing acrylate, which is an effect that is difficult to predict based on the prior art based on the technical solution of the present invention.
[0027] In view of the above synergistic effects, the compounding ratio of alkoxysilane-modified acrylate oligomers and phosphorus-containing acrylates is a key influencing factor. Experimental verification shows that if the proportion of alkoxysilane-modified acrylate oligomers is too large, the flame retardancy of the adhesive system is insufficient, while the viscosity increases significantly, resulting in poor spraying effect. At the same time, the moisture curing speed is too fast, resulting in poor storage performance; and if the proportion of phosphorus-containing acrylates is too large, the adhesion of the cured film obtained after the adhesive is cured to the PCB, especially the adhesion to the PCB with epoxy PCT substrate, is significantly reduced, and it is impossible to meet the level 0 test requirements; therefore, the compounding ratio of alkoxysilane-modified acrylate oligomers and phosphorus-containing acrylates determines the balance of the adhesive in adhesion, flame retardancy and sprayability. Only within the above-mentioned specific compounding ratio range can the best use effect be achieved.
[0028] After testing, the three-proof adhesive of the present invention has the excellent performance of UL94-V0 flame retardancy and 0-level adhesion. At the same time, after testing, the three-proof adhesive also has a dual curing mode, that is, it can be instantly cured into a protective film on the PCB surface where ultraviolet light can be directly irradiated, and in the shadow where ultraviolet light cannot reach, it can also be cross-linked and cured through the reaction of silanization groups and moisture, thereby forming a protective film on the surface of various complex circuit boards to play an effective protective role.
[0029] Considering the application of the three-proof adhesive on the PCB, the adhesive usually needs to meet the spraying process requirements with low viscosity. The viscosity of the adhesive of the present invention is tested to be 200mPa·s~300mPa·s, with good fluidity, meeting the spraying process requirements, and having a good leveling effect on the PCB after spraying.
[0030] Preferably, the UV / moisture dual-curing triple-proof adhesive also includes at least one auxiliary additive, which is a leveling agent, a defoamer, a mildewproof agent or a fluorescent brightener, and the amount of each auxiliary additive added is 1wt.%~3wt.% of the total weight of the alkoxysilane-modified acrylate oligomer, phosphorus-containing acrylate, acrylic reactive diluent and photoinitiator.
[0031] A method for preparing the above-mentioned UV / moisture dual-curing triple-proof adhesive, the preparation steps are: adding an acrylic reactive diluent, a photoinitiator, and auxiliary additives (if any) into a stirrer, stirring in the dark for 1h~2h under vacuum conditions at 25±2°C, and releasing the pressure with nitrogen after stirring evenly; then adding an alkoxysilane-modified acrylate oligomer and a phosphorus-containing acrylate into the stirrer, stirring in the dark for 1h~2h under vacuum conditions at 25±2°C, and releasing the pressure with nitrogen after stirring evenly, so as to prepare the UV / moisture dual-curing triple-proof adhesive; wherein the vacuum conditions are 0.08MPa~0.1MPa, and the stirring speed is 1000r / min~1200r / min.
[0032] A use of the above-mentioned UV / moisture dual-curing triple-proofing adhesive is specifically used for coating on the surface of a printed circuit board substrate to form a protective film after UV curing or moisture curing.
[0033] The adhesive of the present invention is designed based on the chemical structure characteristics of the printed circuit board (PCB) to form a conformal layer that conforms to the contour of the PCB, and the thickness of the protective layer is generally preferably 60μm~150μm to provide effective protection against moisture, dust, chemicals and extreme temperatures. However, since the contours of printed circuit boards are mostly rugged, the adhesive is also required to have dual curing capabilities of UV fast curing and moisture curing to ensure that curing can be achieved in locations that are not exposed to ultraviolet light, which is also a special requirement different from conventional coatings.
[0034] Compared with the prior art, the UV / moisture dual-curing triple-proof adhesive of the present invention not only has the dual-curing properties of UV and moisture, but also has high adhesion and high flame retardancy. Its flame retardancy grade can reach UL94-V0, and its adhesion to PCB after curing can reach level 0. The adhesive has low viscosity, meets the spraying process, has good leveling properties, and can be widely used in various types of circuit boards. In the preparation method, the adhesive preparation method is simple, the raw material and preparation process costs are low, and it does not contain any solvent, meets environmental protection requirements, and has good market application and promotion prospects. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific examples, but the following examples are by no means intended to limit the present invention in any way. Example 1
[0036] An alkoxysilane-modified acrylate oligomer is prepared by the following method:
[0037] S1. Add ethylene glycol diglycidyl ether into a three-necked flask, introduce nitrogen after evacuating, gradually heat to 110° C. under stirring, and slowly add acrylic acid 3 times the molar amount of ethylene glycol diglycidyl ether and p-hydroxyanisole 0.001 times the molar amount of ethylene glycol diglycidyl ether during the heating process; stir the reaction mixture at 110° C. for 10 hours to prepare a prepolymer A;
[0038] Among them, the chemical structural formula of ethylene glycol diglycidyl ether is: , n=1;
[0039] S2. Add prepolymer A and methyl orthosilicate in a molar ratio of 1:1.2 into a reaction bottle under a vacuum environment with nitrogen gas flowing, and then add dibutyltin dilaurate in an amount of 0.4wt.% based on the weight of prepolymer A, and stir the reaction mixture at 80°C for 6h to prepare a UV and moisture dual-curing alkoxysilane-modified acrylate oligomer. Example 2
[0040] An alkoxysilane-modified acrylate oligomer is prepared by the following method:
[0041] S1. Add polyethylene glycol diglycidyl ether into a three-necked flask, introduce nitrogen after evacuating, gradually heat up to 110° C. under stirring, and slowly add 3 times the molar amount of ethylene glycol diglycidyl ether of methacrylic acid and 0.001 times the molar amount of ethylene glycol diglycidyl ether of p-benzoquinone during the heating process; stir the reaction mixture at 110° C. for 12 hours to prepare prepolymer A;
[0042] Wherein, the chemical structural formula of polyethylene glycol diglycidyl ether is: , n=2;
[0043] S2. Add prepolymer A and ethyl orthosilicate in a molar ratio of 1:1.1 into a reaction bottle under a vacuum environment with nitrogen gas flowing, and then add dibutyltin dilaurate in an amount of 0.4wt.% based on the weight of prepolymer A, and stir the reaction mixture at 80°C for 5h to prepare a UV and moisture dual-curing alkoxysilane-modified acrylate oligomer. Example 3
[0044] An alkoxysilane-modified acrylate oligomer is prepared by the following method:
[0045] S1. Add equal molar amounts of ethylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether into a three-necked flask, introduce nitrogen after evacuating, gradually heat to 110° C. under stirring, and slowly add methacrylic acid 3 times the total molar amount of ethylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether and hydroquinone 0.001 times the molar amount of ethylene glycol diglycidyl ether during the heating process; stir the reaction mixture at 110° C. for 12 hours to prepare a prepolymer A;
[0046] Among them, the chemical structural formula of ethylene glycol diglycidyl ether is: , n=1; the chemical structure of polyethylene glycol diglycidyl ether is: , n=4;
[0047] S2. Add prepolymer A and ethyl orthosilicate in a molar ratio of 1:1.2 into a reaction bottle under a vacuum environment with nitrogen gas flowing, and then add dibutyltin dilaurate in an amount of 0.4wt.% based on the weight of prepolymer A, and stir the reaction mixture at 80°C for 5h to prepare a UV and moisture dual-curing alkoxysilane-modified acrylate oligomer.
[0048] The viscosity of the alkoxysilane-modified acrylate oligomers prepared in Examples 1 to 3 was tested using the national standard GB / T2794 test method and a rotational viscometer (Brookfield RV type 7# rotor 100 rpm) test equipment.
[0049] The test results are shown in Table 1 below.
[0050] Table 1:
[0051] Example 4
[0052] A UV- and moisture-drying high-adhesion, high-flame-retardant, three-proof adhesive comprises, by weight, 25 parts of alkoxysilane-modified acrylate oligomers, 20 parts of phosphorus-containing acrylates, 50 parts of acrylic acid-based reactive diluents, and 5 parts of photoinitiators; wherein the alkoxysilane-modified acrylate oligomer is the oligomer prepared in Example 1; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate; the acrylic acid-based reactive diluent is a mixture of 20 parts of tetrahydrofurfuryl methacrylate, 20 parts of isobornyl acrylate, and 10 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 184 and 1.5 parts of photoinitiator TPO. Example 5
[0053] A UV- and moisture-drying high-adhesion, high-flame-retardant, three-proof adhesive comprises, by weight, 27 parts of an alkoxysilane-modified acrylate oligomer, 32 parts of a phosphorus-containing acrylate, 36 parts of an acrylic reactive diluent, and 5 parts of a photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer product prepared in Example 2; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate; the acrylic reactive diluent is a mixture of 6 parts of tetrahydrofurfuryl methacrylate, 15 parts of isobornyl acrylate, and 15 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 1173 and 1.5 parts of photoinitiator TPO. Example 6
[0054] A UV- and moisture-drying high-adhesion, high-flame-retardant, three-proof adhesive comprises, by weight, 25 parts of an alkoxysilane-modified acrylate oligomer, 25 parts of a phosphorus-containing acrylate, 45 parts of an acrylic reactive diluent, and 4.5 parts of a photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer product prepared in Example 1; the phosphorus-containing acrylate is a mixture of 15 parts of diethyl methyl acrylate phosphate and 10 parts of dimethyl ethyl acrylate phosphate; the acrylic reactive diluent is a mixture of 15 parts of tetrahydrofurfuryl methacrylate, 5 parts of isobornyl acrylate, and 25 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 2 parts of photoinitiator 1173, 1 part of photoinitiator 184, and 1.5 parts of photoinitiator TPO. Example 7
[0055] A UV- and moisture-drying high-adhesion, high-flame-retardant, three-proof adhesive comprises, by weight, 26 parts of an alkoxysilane-modified acrylate oligomer, 26 parts of a phosphorus-containing acrylate, 43 parts of an acrylic reactive diluent, and 5 parts of a photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer product prepared in Example 2; the phosphorus-containing acrylate is ethyl dimethyl acrylate; the acrylic reactive diluent is a mixture of 10 parts of tetrahydrofurfuryl methacrylate, 23 parts of isobornyl acrylate, and 10 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3 parts of photoinitiator 1173 and 2 parts of photoinitiator 184. Example 8
[0056] A UV- and moisture-drying high-adhesion, high-flame-retardant, three-proof adhesive comprises, by weight, 23 parts of alkoxysilane-modified acrylate oligomers, 25 parts of phosphorus-containing acrylates, 37 parts of acrylic acid-based reactive diluents, and 4.5 parts of photoinitiators; wherein the alkoxysilane-modified acrylate oligomers are the oligomer products prepared in Example 3; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate; the acrylic acid-based reactive diluent is a mixture of 7 parts of tetrahydrofurfuryl methacrylate and 30 parts of isobornyl acrylate; and the photoinitiator is a mixture of 1 part of photoinitiator 1173, 4 parts of photoinitiator 184, and 0.5 parts of photoinitiator TPO.
[0057] Comparative Example 1:
[0058] An adhesive is composed of 27 parts by weight of pure acrylic resin 65357 produced by Changxing Company, 32 parts of phosphorus-containing acrylate, 36 parts of acrylic reactive diluent and 4.5 parts of photoinitiator; wherein the phosphorus-containing acrylate is diethyl methyl phosphate acrylate, the acrylic reactive diluent is a mixture of 6 parts of tetrahydrofurfuryl methacrylate, 15 parts of isobornyl acrylate and 15 parts of propylene glycol monomethyl ether diacrylate; the photoinitiator is a mixture of 3.5 parts of photoinitiator 1173 and 1.5 parts of photoinitiator TPO.
[0059] Comparative Example 2:
[0060] An adhesive is composed of 25 parts by weight of alkoxysilane-modified acrylate oligomer, 20 parts of pure acrylic resin 65357 produced by Changxing Company, 50 parts of acrylic reactive diluent and 5 parts of photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer prepared in Example 1; the acrylic reactive diluent is a mixture of 20 parts of tetrahydrofurfuryl methacrylate, 20 parts of isobornyl acrylate and 10 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 184 and 1.5 parts of photoinitiator TPO.
[0061] Comparative Example 3:
[0062] An adhesive is composed of 24 parts by weight of an alkoxysilane-modified acrylate oligomer, 35 parts of a phosphorus-containing acrylate, 36 parts of an acrylic reactive diluent, and 5 parts of a photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer product prepared in Example 2; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate; the acrylic reactive diluent is a mixture of 6 parts of tetrahydrofurfuryl methacrylate, 15 parts of isobornyl acrylate, and 15 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 1173 and 1.5 parts of photoinitiator TPO.
[0063] Comparative Example 4:
[0064] An adhesive is composed of 35 parts by weight of an alkoxysilane-modified acrylate oligomer, 24 parts of a phosphorus-containing acrylate, 36 parts of an acrylic reactive diluent, and 5 parts of a photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer product prepared in Example 2; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate; the acrylic reactive diluent is a mixture of 6 parts of tetrahydrofurfuryl methacrylate, 15 parts of isobornyl acrylate, and 15 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 1173 and 1.5 parts of photoinitiator TPO.
[0065] Comparative Example 5:
[0066] An adhesive is composed of 27 parts by weight of acrylic acid ester of pure acrylic resin 65357 of Changxing Company, 50 parts of phosphorus-containing acrylic acid ester, 21 parts of acrylic acid active diluent and 5 parts of photoinitiator; wherein the alkoxysilane-modified acrylic acid ester oligomer adopts the oligomer product prepared by Example 2; the phosphorus-containing acrylic acid ester adopts diethyl methyl phosphate acrylate; the acrylic acid active diluent adopts a mixture of 6 parts of tetrahydrofurfuryl methacrylate, 10 parts of isobornyl acrylate and 5 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator adopts a mixture of 3.5 parts of photoinitiator 1173 and 1.5 parts of photoinitiator TPO.
[0067] Comparative Example 6:
[0068] An adhesive is composed of 45 parts by weight of an acrylate oligomer modified by ultraviolet light and dual-curing alkoxysilane, 20 parts of a phosphorus-containing acrylate, 30 parts of an acrylic reactive diluent, and 5 parts of a photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer product prepared in Example 2; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate; the acrylic reactive diluent is a mixture of 10 parts of tetrahydrofurfuryl methacrylate, 8 parts of isobornyl acrylate, and 12 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 1173 and 1.5 parts of photoinitiator TPO.
[0069] Comparative Example 7:
[0070] An adhesive is composed of 25 parts by weight of dual-curing resin 6133N-10 produced by Changxing Company, 20 parts of phosphorus-containing acrylate, 50 parts of acrylic acid active diluent and 5 parts of photoinitiator; wherein the alkoxysilane-modified acrylate oligomer is the oligomer prepared by Example 1; the phosphorus-containing acrylate is diethyl methyl phosphate acrylate, the acrylic acid active diluent is a mixture of 20 parts of tetrahydrofurfuryl methacrylate, 20 parts of isobornyl acrylate and 10 parts of propylene glycol monomethyl ether diacrylate; and the photoinitiator is a mixture of 3.5 parts of photoinitiator 184 and 1.5 parts of photoinitiator TPO.
[0071] The preparation method of the UV- and moisture-cured high-adhesion, high-flame-retardant, three-proof adhesive of Examples 4 to 8 and the adhesive of Comparative Examples 1 to 7 is as follows: first, add an acrylic reactive diluent and a photoinitiator to a stirrer, stir in a vacuum environment at 25±2°C, avoid light for 1 hour, and release the nitrogen pressure after stirring and mixing evenly; then continue to add the remaining two components to the stirrer, also place in a vacuum environment at 25±2°C, stir in a vacuum environment at 25±2°C for 2 hours, and release the nitrogen pressure after stirring and mixing evenly to obtain the adhesive. The vacuum condition is 0.08MPa~0.1MPa, and the stirring speed is 1000r / min~1200r / min.
[0072] Performance Test:
[0073] The high adhesion and high flame retardant triple-proof adhesives prepared by UV and moisture dual curing in Examples 4 to 8, and the adhesives of Comparative Examples 1 to 7 were subjected to UV curing surface dry energy test, pure moisture curing time test, flame retardant grade test, adhesion grade test, and spraying effect test in sequence.
[0074] The UV-curing surface drying energy test method is: use a high-pressure mercury lamp to irradiate the adhesive layer coated on the surface of the PCB substrate, and use the finger touch method to judge the surface drying, that is, the finger is required to touch the surface of the coating lightly and no stickiness is felt; then the surface drying energy is tested by an optical power density meter.
[0075] The test method for pure moisture curing time is as follows: place the sample formed by the adhesive layer coated on the surface of the PCB substrate in a constant temperature and humidity chamber (25±2℃, 50±10%RH) in the dark, take it out every 2 hours, and judge whether the sample is cured; specifically, drop acetone on the surface of the sample. If the sample dissolves quickly, it means that it is not completely cured; otherwise, it proves that it is completely cured.
[0076] Flame retardant grade test method: UV curing energy condition is 1000mj / cm 2 , moisture curing time condition is 80h, and tested according to UL94 standard.
[0077] Adhesion level test method: UV curing energy condition is 1000mj / cm 2 The moisture curing time condition is 80h. PCB circuit board is selected as the substrate for coating the adhesive and tested in accordance with GB / T 9286-2021 standard.
[0078] Spraying effect test method: spray the adhesive on the surface of the substrate, and measure the film thickness with a film thickness meter after UV curing: if the film thickness can reach 50μm~150μm, it means that the spraying requirements are met. If the film thickness is thicker than the above standard no matter how the equipment is debugged, it does not meet the spraying requirements; at the same time, observe the surface state of the film with the naked eye. If the film surface is smooth, it means that the leveling effect is good. If there are ripples on the film surface, it means that the leveling effect is poor. After the above two tests, if both the film thickness and the leveling effect meet the requirements, the spraying test result is good. If any of the film thickness and the leveling effect does not meet the requirements, the spraying test result is poor.
[0079] The performance test results of Examples 4 to 8 and Comparative Examples 1 to 7 are shown in Table 2 below.
[0080] Table 2:
[0081]
[0082] From the data of the embodiments and comparative examples in the table, it can be concluded that:
[0083] The triple-proof adhesive prepared by Example 4 to Example 8 has dual curing capabilities of UV curing and moisture curing, and is sprayable. The cured adhesive film obtained after curing meets the UL94-V0 flame retardant rating and also has grade 0 adhesion, and has good product performance.
[0084] Compared with Example 2, during the preparation process of the adhesive of Comparative Example 1, the alkoxysilane-modified acrylate oligomer is replaced with pure acrylate. Although it uses the same phosphorus-containing flame retardant component as Example 2, the acrylate lacks the alkoxysilane modification feature, which makes the silicon-phosphorus synergistic flame retardant effect invalid, resulting in a significant decrease in the flame retardancy of the cured adhesive film.
[0085] On the basis of Comparative Example 1, in Comparative Example 5, the adhesive prepared by further increasing the amount of phosphorus-containing acrylate added can achieve a flame retardant grade of UL94-V0, but due to the excessively high proportion of phosphorus-containing acrylate added, the adhesion to the PCB is further reduced.
[0086] Compared with Example 1, in the preparation process of the adhesive of Comparative Example 2, pure acrylic resin is used to completely replace the phosphorus-containing acrylate, resulting in that the cured film of the adhesive has no flame retardant effect at all.
[0087] Compared with Example 2, during the preparation process of the adhesive of Comparative Example 3, the total weight of the alkoxysilane-modified acrylate oligomer and the phosphorus-containing acrylate is the same as that of Example 2, but the ratio of the phosphorus-containing acrylate to the alkoxysilane-modified acrylate oligomer exceeds the ratio, resulting in that although the cured film of the adhesive can achieve the flame retardant effect of UL94-V0 level, the adhesion of the formed cured film to the PCB is significantly reduced and cannot meet the use requirement of level 0.
[0088] Compared with Example 2, during the preparation process of the adhesive of Comparative Example 4, the total weight of the alkoxysilane-modified acrylate oligomer and the phosphorus-containing acrylate is the same as that of Example 2, but the ratio of the phosphorus-containing acrylate to the alkoxysilane-modified acrylate oligomer is lower than the appropriate ratio, resulting in that although the adhesion of the cured adhesive film can reach level 0, the flame retardant level is reduced and the spraying effect is average.
[0089] On the basis of Comparative Example 4, the addition ratio of alkoxysilane-modified acrylate oligomer was further increased in Comparative Example 6. Although the flame retardant grade was slightly improved, the viscosity of the adhesive increased significantly, and it was basically impossible to spray. In addition, the moisture curing speed was too fast, and the storage performance became poor.
[0090] Compared with Example 1, in the adhesive preparation process of Comparative Example 7, although the chemical structure of the polyurethane acrylate contains UV-curable acryloxy groups and moisture-curable isocyanate groups, which meet the dual-cure performance, compared with the alkoxysilane-modified acrylate oligomer used in the present application, its adhesion to the printed circuit board is poor, especially after combining with phosphorus-containing acrylate, the adhesion is even worse, and the adhesion cannot reach level 0; and the silicon-phosphorus synergistic flame retardant effect of the adhesive prepared in this comparative example fails, and the flame retardant effect is poor.
[0091] In summary, the adhesive of the present invention is prepared by compounding an alkoxysilane-modified acrylate oligomer and a phosphorus-containing acrylate in a certain proportion to form a synergistic composition, and supplemented with necessary components, so as to obtain a dual-curing property of ultraviolet light and moisture, and the flame retardant grade can reach UL94-V0. After curing, the adhesion to the PCB can reach level 0, and the viscosity is low, which meets the spraying process and has good leveling properties. It can be widely used in the formation of three-proof protective films for various types of PCB circuit boards.
[0092] The above-described embodiments are only preferred examples of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features and principles described in the scope of the patent application of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. A UV and moisture dual-curing high adhesion and high flame retardant three-proof adhesive, characterized in that: The invention comprises 20 to 35 parts by weight of alkoxysilane-modified acrylate oligomer, 20 to 50 parts by weight of phosphorus-containing acrylate, 30 to 70 parts by weight of acrylic reactive diluent and 2 to 10 parts by weight of photoinitiator; wherein: The alkoxysilane-modified acrylate oligomer is an oligomer having a viscosity of 5000 mPa·s to 10000 mPa·s obtained by copolymerizing monomer I, monomer II and monomer III, wherein monomer I is ethylene glycol diglycidyl ether and / or polyethylene glycol diglycidyl ether, monomer II is acrylic acid or methacrylic acid, and monomer III is alkyl orthosilicate; the chemical structural formula of the alkoxysilane-modified acrylate oligomer is: , In the formula, R1 each independently represents a C1~C3 alkyl group, R2 each independently represents H or a methyl group, and n is an integer ranging from 1 to 10; The phosphorus-containing acrylate is at least one of diethyl methyl phosphate acrylate, diethyl ethyl phosphate acrylate, and diethyl methyl phosphate methacrylate; The weight ratio of the alkoxysilane-modified acrylate oligomer to the phosphorus-containing acrylate is (0.8-1.25):
1.
2. The UV / moisture dual-curing conformal adhesive according to claim 1, characterized in that: The preparation method of alkoxysilane-modified acrylate oligomer is as follows: S1. Add monomer I into a three-necked flask, introduce nitrogen after evacuating, gradually heat to 100° C. to 130° C. under stirring, and slowly add monomer II and polymerization inhibitor during the heating process; react the reaction mixture at 100° C. to 130° C. for 10 h to 12 h to prepare prepolymer A; S2. The prepolymer A, alkyl orthosilicate and catalyst are heated to 70°C to 90°C in a vacuum environment with nitrogen gas introduced, and stirred for reaction for 5h to 6h to prepare an alkoxysilane-modified acrylate oligomer which is dual-cured by UV light and moisture.
3. The UV / moisture dual-curing anti-corrosion adhesive according to claim 2, characterized in that: In step S1, the molar ratio of monomer I to monomer II is 1:(2-3); the inhibitor is p-hydroxyanisole, p-benzoquinone, hydroquinone or naphthoquinone; and the amount of the inhibitor added is 0.001 times the molar amount of monomer I.
4. The UV / moisture dual-curing anti-corrosion adhesive according to claim 2, characterized in that: In step S2, the alkyl orthosilicate is methyl orthosilicate, ethyl orthosilicate or propyl orthosilicate; the molar ratio of prepolymer A to the alkyl orthosilicate is 1:(1-1.3); the catalyst is dibutyltin dilaurate; and the amount of catalyst added is 0.3wt.%-0.4wt.% of the weight of prepolymer A.
5. The UV / moisture dual-curing conformal adhesive according to claim 1, characterized in that: The acrylic active diluent is at least one of tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, isobornyl acrylate, isobornyl methacrylate and propylene glycol monomethyl ether diacrylate.
6. The UV / moisture dual-curing conformal adhesive according to claim 1, characterized in that: The photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxy-cyclohexyl-phenylmethanone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
7. The UV / moisture dual-curing conformal adhesive according to claim 1, characterized in that: It also includes at least one auxiliary additive, which is a leveling agent, a defoaming agent, a mildewproofing agent or a fluorescent whitening agent, and the amount of each auxiliary additive added is 1wt.%~3wt.% of the total weight of the alkoxysilane-modified acrylate oligomer, the phosphorus-containing acrylate, the acrylic active diluent and the photoinitiator.
8. A method for preparing a UV / moisture dual-curing conformal adhesive as claimed in any one of claims 1 to 7, characterized in that: The preparation steps are as follows: adding other components except oligomers and phosphorus-containing acrylates into a stirrer, stirring for 1 h to 2 h in a vacuum condition at 25±2°C in a light-proof manner, and releasing the pressure with nitrogen after stirring evenly; then adding oligomers and phosphorus-containing acrylates into the stirrer, stirring for 1 h to 2 h in a vacuum condition at 25±2°C in a light-proof manner, and releasing the pressure with nitrogen after stirring evenly, thereby preparing a UV / moisture dual-curing triple-proof adhesive; wherein the vacuum condition is 0.08 MPa to 0.1 MPa, and the stirring speed is 1000 r / min to 1200 r / min.
9. A use of the UV / moisture dual-curing conformal adhesive as claimed in claim 1, characterized in that: Used to coat the surface of printed circuit board substrate to form a protective film.
